EVALUATION OF BUDGETING METHODS FOR MAINTENANCE OF HERITAGE BUILDINGS - Lekarapa, Martin; Grobbelaar, Schalk (The South African Journal of Industrial Engineering, 2022)
Heritage buildings have evolved into development catalysts that, when properly maintained, can improve their surrounding area’s liveability while sustaining productivity in an ever-changing global context. Unfortunately, the high uncertainty involved in preserving heritage buildings frequently leads to over-budget projects. This article evaluates the factors that contribute to projects being over budget and the methods used to develop project budgets. History-based budgeting methods, value-oriented budgeting methods, analytical budgeting methods, and budgeting by condition description are frequently used, while new artificial intelligence models are also emerging. In addition, the review considers the Monte Carlo method and compares it with artificial intelligence models. Considering the high uncertainty involved when maintaining heritage buildings, it is concluded that the Monte Carlo method could be a very effective tool. For this reason, it is recommended that its use be tested on heritage building projects.